Cutting tool standardization - Ostapenko Maria; Voronova Natalya (MATEC Web of Conferences, 2021)
The article aims to determine the role of standardization in the engineering industry and for cutting tools in general. This paper explains the basic principles of standardization. The technical committee for standardization of cutting tools (TC 95 ‘Tools’) was presented. The main directions of work and functions of TC 95 ‘Tools’ are explained. Harmonization of standards in Russia is presented on the example of ISO 13399 international standard. The work reveals positive aspects of officially translated versions of standards for enterprises. The article also describes the role of standardized tools when working in computer-aided design systems (CAD).